2014
DOI: 10.1302/0301-620x.96b6.32721
|View full text |Cite
|
Sign up to set email alerts
|

Fragility fractures of the ankle in the frail elderly patient

Abstract: Conventional methods of treating ankle fractures in the elderly are associated with high rates of complication. We describe the results of treating these injuries in 48 frail elderly patients with a long calcaneotalotibial nail. The mean age of the group was 82 years (61 to 96) and 41 (85%) were women. All were frail, with multiple medical comorbidities and their mean American Society of Anaesthesiologists score was 3 (3 to 4). None could walk independently before their operation. All the fractures were displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 25 publications
2
88
2
1
Order By: Relevance
“…Therefore, it should only be an option in bedridden patients. 41 Hindfoot fusion with specially designed, curved nails is an excellent treatment option for patients with Charcot neurogenic osteoarthropathy of the ankle/hindfoot type (Sanders IV), because standard techniques of internal fixation will invariably fail in these patients. 17 Alternatively, a small wire external fixator may be used.…”
Section: Techniques Of Fixationmentioning
confidence: 99%
“…Therefore, it should only be an option in bedridden patients. 41 Hindfoot fusion with specially designed, curved nails is an excellent treatment option for patients with Charcot neurogenic osteoarthropathy of the ankle/hindfoot type (Sanders IV), because standard techniques of internal fixation will invariably fail in these patients. 17 Alternatively, a small wire external fixator may be used.…”
Section: Techniques Of Fixationmentioning
confidence: 99%
“…It allows the patient to mobilize immediately. Al Namari et al studied 48 frail elderly patients with displaced ankle fractures who were treated with a long calcaneotalotibial nail [26•]. The mean age of the group was 82 years (61 to 96) and 85% were females.…”
Section: Introductionmentioning
confidence: 99%
“…Complications included superficial infection (4%), deep infection (2%), a broken or loose distal locking screw (6%), valgus malunion (4%), and one below-knee amputation following an unsuccessful vascular operation. There were no cases of nonunion, nail breakage, or peri-prosthetic fracture [26•]. Jonas et al studied 31 patients with a short retrograde tibiotalar-calcaneal nail and found no postoperative wound problems [27].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who are not independently mobile are at an elevated risk of complications, such as pressure sores, pneumonia, and deep vein thrombosis, and their mortality is increased from these conditions. Treatment that enables weightbearing as rapidly as possible following surgery leads to better prognosis in older patients [1,2]. Therefore, if there is severe soft tissue damage, early amputation can be performed in order to shorten the time required until the patient is bearing weight with the prosthesis.…”
Section: Discussionmentioning
confidence: 99%